The symbols of kazakh trophes (Journal of history, 2019)
The urgency and novelty of the topic are justified by the emerging attention of the world community to the comprehension of the collective unconscious in ethnic cultures. In this context, the stated goal – the identification of the role of the archetypal matrix in the origin and symbolism of the crests of Kazakhstan is quite justified. What is new is the very formulation of the problem – the interpretation ofthe meaning of the essence of a particular object of the Kazakh culture- the crest, and the scale of itscomprehension in the mainstream of world traditions. The main idea of the work is the disclosure of therole of archetypes in the emergence of uniform categories of hygiene products (combs) with the commonnessof their semantic content on a planetary scale. The purpose of the article is to identify the archetypalmatrixes in the origins and symbolism of Kazakhstan’s crests in the global context. As a method,a systematic, including a historical-comparative, complex analysis of crests using data from interdisciplinarysciences (archeology, ethnology, art criticism, semiotics, folklore studies) is used as a method.Main research results. In the emergence of the design of the crest, apparently, the archaic worldview ofman was shown about the opposition of two dual forces. Demonic evil spirits, i.e. parasites, threateninghealth, were contrasted with carved teeth, associated with the terrifying teeth of predators. In this,it can be said, that the involvement of ambivalent code – one of the archetypal matrix of the collectiveunconscious – is traced. The idea of the magic cathartic and at the same time protective force of bonecombs was formed on the basis of the fusion of the sanitary functions of the object and its contact withthe «life energy» of hair, the semantics of which arose much earlier. All this was the reason for the discoveryin ancient burials of Kazakhstan and many other countries of the world of general categories ofobjects: amulets for decorating ceramics, combs for combing hair and comb-hairpins for hair. Over time,the crests were filled with new decorative ideas in accordance with ethnic characteristics and artisticevolution. The original symbolic core of the crests in the course of its development acquired additionalthought-forms. Due to sign content, the image of the crest, with intonations of miraculous magic, wasreflected in related areas of Kazakh folk art. In general, the results of the article have made significanttheoretical additions to the problem of the etiology of cultural community on a global scale.